2017
DOI: 10.1016/j.jtcme.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Authentication of Piper betle L . folium and quantification of their antifungal-activity

Abstract: The TLC profiles of intra- and inter-day precision for Piper betle L. (PBL) folium methanol extract was studied for their peak marker recognition and identification. The Numerical chromatographic parameters (NCPs) of the peak markers, the hierarchical clustering analysis (HCA) and the principal component analysis (PCA) were applied to authenticate the PBL. folium extract from other Piper species folium extract and to ensure the antifungal activity quality of the PBL essential oil. The spotted extract was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Using PCA, antifungal activity can be determined from the first component's PCA, which linearly correlated to the biomarker used. This method proved it can be used to predict the antifungal activity from P. betle L. (Wirasuta et al, 2017).…”
Section: Activity and Quality Determinationmentioning
confidence: 86%
See 2 more Smart Citations
“…Using PCA, antifungal activity can be determined from the first component's PCA, which linearly correlated to the biomarker used. This method proved it can be used to predict the antifungal activity from P. betle L. (Wirasuta et al, 2017).…”
Section: Activity and Quality Determinationmentioning
confidence: 86%
“…The result of PCA and HCA was comparable and the three principal components accounted for >80.5%. The other studies conducted similar analysis and concluded that chemometrics PCA and HCA allowed the discrimination between the varieties based on metabolite fingerprint or volatile compounds (Azemin et al, 2018;Maulidiani et al, 2012;Srisopon et al, 2019;Wirasuta et al, 2017) Meanwhile, Rafi et al ( 2018) identified and discriminated Curcuma species. All of the four species are closely related and used as herbal drinks and food supplements in Indonesia.…”
Section: Species Classificationmentioning
confidence: 95%
See 1 more Smart Citation
“…Though the mode of the study was purely related to pharmaceutical authenticity of the components depending on PCA and HCA profiling. The method was not able to differentiate Piper nigrum from Piper betle cluster and was not strong enough to differentiate cultivars under Piper betle species (Wirasuta et al, 2016). Though the TLC-densitometric study of different commercial varieties and heterogeneous relative frequency (hRf) value based discrimination could be applied to assess the level of cultivar complexity.…”
Section: Conversion Of Metabolomic Data To Genomic Marker For Geneticmentioning
confidence: 99%
“…The analytical method should provide the phytochemical fingerprint, which utilizes the authenticity and quality control of raw material and the preparations. 4 The Raman spectrum offers qualitative and quantitative information of the measured substances. The handheld Raman could be used for field quality control of curcumin contain in the turmeric rhizome.…”
mentioning
confidence: 99%